Does the height matter? a case for wi-fi based wireless positioning system - Ismail, Abdul Halim; Sunang, Godrey Amos; Azmi, Muhamad Safwan Muhamad; Ayob, Mohd Nasir; Hashim, Mohd Sani Mohamad; Basri, Hassrizal Hassan; Widyasmoro, Widyasmoro; Ismail, Mohd Muzafar (2023)
Wireless Positioning System (WPS) is an emerging field rises with the aim to minimize the development and algorithm cost as well as applicable in many applications. The methods are rather straightforward compared to the use of conventional on-board sensing elements that often require fusion of several sensors as well as complex algorithms. Wireless Fidelity (Wi-Fi) is the choice of elements in WPS due to wide availability as well as use of existing infrastructure. One interesting factor to consider in obtaining higher positioning accuracy is to assess the Wi-Fi height level. Many previous studies proposed optimization of the Wi-Fi antenna heights, but our direction is towards experimental works to observe if the antenna heights does matter or is it a totally insignificant parameter. Three different analyses were conducted on the data, which are statistical, two-layer average and quotient calculations. The results are validated for our experiments heights from 0.5 to 2.0 meter.